Hippocampal and Left Subcallosal Anterior Cingulate Atrophy in Psychotic Depression - Bijanki, Kelly Rowe; Hodis, Brendan; Brumm, Michael C.; Harlynn, Emily L.; McCormick, Laurie M. (PLOS ONE, 2014)
Background Psychotic depression is arguably the most diagnostically stable subtype of major depressive disorder, and an attractive target of study in a famously heterogeneous mental illness. Previous imaging studies have identified abnormal volumes of the hippocampus, amygdala, and subcallosal region of the anterior cingulate cortex (scACC) in psychotic depression, though studies have not yet examined the role of family history of depression in these relationships. Methods 20 participants with psychotic depression preparing to undergo electroconvulsive therapy and 20 healthy comparison participants (13 women and 7 men in each group) underwent structural brain imaging in a 1.5 T MRI scanner. 15 of the psychotic depression group had a first-degree relative with diagnosed affective disorders, while the healthy control group had no first-degree relatives with affective disorders. Depression severity was assessed with the Hamilton Depression Rating Scale and duration of illness was assessed in all patients. Automated neural nets were used to isolate the hippocampi and amygdalae in each scan, and an established manual method was used to parcellate the anterior cingulate cortex into dorsal, rostral, subcallosal, and subgenual regions. The volumes of these regions were compared between groups. Effects of laterality and family history of affective disorders were examined as well. Results Patients with psychotic depression had significantly smaller left scACC and bilateral hippocampal volumes, while no group differences in other anterior cingulate cortex subregions or amygdala volumes were present. Hippocampal atrophy was found in all patients with psychotic depression, but reduced left scACC volume was found only in the patients with a family history of depression. Conclusions Patients with psychotic depression showed significant reduction in hippocampal volume bilaterally, perhaps due to high cortisol states associated with this illness. Reduced left scACC volume may be a vulnerability factor related to family history of depression.